PRESENCE OF EVIDENCE OF MEDICAL RECORD CONTENTS IN TRIALS FOR CRIMINAL ACTIONS OF MALPRACTICE BASED ON MINISTER OF HEALTH REGULATIONS NUMBER 269/MENKES/PER/2008 JUNCTO LAW NUMBER 8 OF 1981 CONCERNING THE BOOK OF CRIMINAL PROCEDURES - David Mallisa Allorante; Margo Hadi Pura (Universitas Labuhanbatu, 2024)
Victimology, from the words victim (victim) and logic (science), Latin victim (victim) and logos (science). In simple terms, victimology means the science of victims (crimes). According to the Crime Dictionary dictionary quoted by an Abussalam expert, victims are